Economic Notes: 1999–2011. (1st February 2023) - Roma, Antonio
Abstract: The paper documents that, over the period 1999–2011, Economic Notes made a further step forward in becoming a professional outlet for high‐quality academic research by moving under the production and distribution by an international publisher (Blackwell, later on, Wiley). The Journal cultivated research on the challenges posed by an environment of financial innovation and security‐market expansion, which posed new economic policy and bank management issues. Accordingly, it refocused on compelling financial, banking and monetary topics, as epitomized by adopting its current subtitle 'Review of Banking, Finance and Monetary Economics'. On balance, the Journal 's long‐standing editorial policy of being open to a variety of contributions in the field of economics was retained, but a noticeable shift toward financial themes took shape over the 1999–2011 period. This focus, inspired by the events of the period, helped the Journal to remain relevant to the research interests of many scholars at the time. Notably, the Journal included topics in applied research that had a potential impact on the management of financial institutions, such as risk management and asset pricing, as well as the analysis of financial regulations. Those years proved fertile for both editorial policy and the dissemination of the Journal .